STUDI PENGARUH PERIKLANAN, PROMOSI MONETER, DAN PERSEPSI ETIKA TERHADAP LOYALITAS MEREK BEDAK TABUR MUKA SARIAYU - Dewi, Ade Puspita; Sukresna, I Made (Faculty of Economics and Business Diponegoro University, 2020)
Based on the percentage of the Sariayu brand in the Top Brand Index, it has increased and decreased. From the Top Brand Index data, it can be seen that in 2016 the percentage of powder face products was 8.3%. In 2017 it decreased to 8.0%. In 2018 sales rose to 10.4% but in 2019 there was a drastic decline of 5.9% with the figure reaching 4.5%. From these data it is known that Sariayu products for 3 consecutive years ranked number 4 and then dropped to number 5.This study aims to analyze the impact of advertising, monetary promotion, ethical perceptions, perceived quality and social media on brand loyalty conducted on Sariayu cosmetic users. In this study using advertising variables, monetary promotion, and ethical perception as an independent variable, perceived quality as an intervening variable, social media as a moderator variable and brand loyalty as the dependent variable.The population in this study was Sariayu cosmetic users. The number of samples used were 200 respondents. Data obtained from the questionnaire were processed and analyzed using the AMOS and SPSS programs.The results of this study indicate that advertising has a positive and significant effect on perceived quality, monetary promotion has no significant effect on perceived quality, ethical perceptions have a positive and significant effect on perceived quality, advertising moderated by social media does not have a significant effect on perceived quality, monetary promotion has moderated social media does not have a significant effect on perceived quality, ethical perceptions moderated by social media do not have a significant effect on perceived quality, and perceived quality has a positive and significant effect on brand loyalty.